Chế tạo và nghiên cứu tính chất vật liệu polyme nanoclay compozit trên cơ sở blend cao su thiên nhiên và cao su butadien styren - Phong và cộng sự, Võ Thành (Vietnam Journal of Chemistry, 2014)
Elastomer nanocomposites consisting of blend of natural rubber and styrene butadiene rubber (NR/SBR) and layered silicate (nanoclay) are preared successfully by emulsion method. The characterization of rubber-clay nanocomposites have been investigated by XRD and TEM. The TEM showed clay had been dispersed to one or several layers. The XRD showed that basal spacing in the clay was increased. It was evident that the clay layer could be uniformly dispersed in the rubbers matrix on nanometer level. The best reinforcing effect of nanoclay reached when ration of layered silicates is 5 wt%.